Penerapan Media Pembelajaran Berbasis Autoplay Media Studio Untuk Meningkatkan Keterampilan Membaca Teks Puisi Pada Siswa Kelas II SD - Konradus Silvester Jenahut; Osniman Paulina Maure (Journal on Education, 2021)
This research departs from the problems experienced by second grade elementary school students in learning to read poetry, such as the lack of students' interest in poetry, teachers who are not good at demonstrating interesting poetry readings, the absence of interesting learning media for reading poetry material, and the ability to read poetry at school. students receive less attention from both Indonesian language teachers and teachers of other fields of study. This study aims to improve the process and student learning outcomes in learning to read poetry by applying learning media based on Auto Play Media Study. This research is a type of Classroom Action Research (PTK) by adopting the PTK design model Kemmis & Taggart, (1981). Data collection techniques in this study, namely interviews, observation, tests and documentation. Based on the research results, there was a significant increase in student learning outcomes, especially in poetry reading ability tests. Where in cycle 1 the average score obtained by students was 69.06 and there was an increase in learning outcomes in cycle 2 with an average score of 76.88. Thus the application of learning media based on Auto Play Media Studio to poetry reading materials in grade II elementary schools can improve student learning processes and outcomes.